Introduction of different apitherapy houses and their consumer assessment - Simonné Agócs, Kata Eszter; Szabó, Rubina Tünde (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Apitherapy is that natural substances, produced by honey bees, can be used in medicine. In the apitherapy house, the vibration, the temperature and the smell of the hive can affect the body positively. The aim of the study was to survey of the knowledge about honey bee products and apitherapy houses. Three bee keeper were interviewed. An apiterapeute has been using her one-man apitherapy house only as a treatment. The owner of the largest apitherapy house in Hungary was interviewed. In his house, it is possible to attend a group and listen to a lecture about apitherapy and honey bees, but patients receive their treatment too. A Transylvanian beekeeper, welcomes seriously ill patients free of charge in her small, two-man apitherapry house, but the house is also open to tourists. A survey was created and completed by 184 participants of different ages and genders via a social networking site. It is clear from the responses, that there is a need for a better understanding of apitherapy. According to Polish research, a third of survey respondents, and more than two thirds of our responders, would like to try apitherapy house. The best way to raise awareness would be to give inform through social networking sites. In addition, open days, various programmes and lectures could generate impact.
Keywords: apitherapy house; apitherapy; apiculture